Digital Transformation and Psychological Welfare at MNC Bank Makassar Branch - Tribuana, Dhimas; Narimawati, Umi; Syafei, M. Yani (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
In the era of digital transformation, the banking industry, particularly in Indonesia, has experienced significant growth, with a 22.13% annual increase in digital transactions. This study investigates the influence of digital transformation on employee psychological well-being, focusing on the MNC Bank Makassar Branch. Using explanatory and quantitative methods, questionnaires were administered to all 37 employees. Results indicate a positive and significant relationship between digital transformation and psychological well-being, explaining 37% of the variance. Overall evaluation yielded excellent results (87%). The study underscores the importance of enhancing technology adoption, digital data exchange, and IT competence to promote employee well-being. Future research should explore additional variables for a comprehensive understanding.